The impact of translational studies in the current management of osteoporosis - Dontas, Ismene A.; Lambrou, George I. (Annals of Research Hospitals, 2019)
Recent technological and scientific advancements have changed the way through which knowledge is acquired through research. Until the early 1980s, research that was not hypothesis-oriented was considered an “anathema” within the scientific world. With the advent of high throughput methodologies in the early 1990s, a new approach to scientific research was created, namely “discovery-driven” research. These “opposite” approaches produced another discipline, named “translational research” (TR). In this sense, the investigation of diseases, such as osteoporosis, changed drastically. Osteoporosis is characterized by decreased bone mass and a deterioration of bone microarchitecture, leading to enhanced fragility and a subsequent increase in fracture risk. Osteoporosis is also known with the term “silent disease”, since it is often undetected until a low-energy fragility fracture occurs, which triggers further diagnosis and therapy. High throughput methodologies, combined with in vitro and in vivo studies have the potential to lead us to new prognostic and therapeutic targets of osteoporosis management. In the present work we review some of the important concepts of TR in the treatment and the future of osteoporosis. We have emphasized on the description of genomics and the use of in vitro and in vivo systems towards the understanding of osteoporosis pathogenesis and treatment.